Critical Care Nurses’ Adherence to Ethical Codes and Its Association with Spiritual Well-Being and Moral Sensitivity - Marzieh Momennasab; Zohreh Homayoon; Camellia Torabizadeh (Critical Care Research and Practice, 2023)
Background. Adherence to ethical codes is a major pillar of nursing care that is affected by various factors. Identifying these factors can lead to better ethical performance. The present study was conducted to determine critical care nurses’ adherence to ethical codes and its association with spiritual well-being (SWB) and moral sensitivity (MS). Methods. In this descriptive-correlational study, data were collected using the moral sensitivity questionnaire (MSQ) by Lützén et al., Paloutzian and Ellison’s spiritual well-being scale (SWBS), and the adherence to ethical codes questionnaire. The study was conducted on 298 nurses working in critical care units of hospitals affiliated with Shiraz University of Medical Sciences in southern Iran in 2019. This study was examined and approved by the Ethics Committee of Shiraz University of Medical Sciences. Results. The majority of the participants were female (76.2%) and single (60.1%), with a mean age of 30.69 ± 5.74 years. The mean scores of adherence to ethical codes, SWB, and MS were 64.06 (good), 91.94 (moderate), and 134.08 (moderate), respectively. Adherence to ethical codes had a positive correlation with the total score of SWB (P<0.001, r = 0.25) and MS (P<0.001, r = 0.27). A positive correlation was also observed between MS and SWB (P<0.001, r = 0.41). Meanwhile, MS (β = 0.21) had a greater effect than SWB (β = 0.157) on adherence to ethical codes. Conclusion. Critical care nurses showed a good adherence to ethical codes. MS and SWB also positively affected their adherence to ethical codes. Nursing managers can use these findings to devise plans for the promotion of MS and SWB in nurses and thus help improve their ethical performance.